Organizational justice, organizational learning and organizational image on engagement of young employees in commercial banks / Ibiwani Alisa Hussain - Hussain, Ibiwani Alisa (2015)
Young employees in organizations are becoming more demanding concerning justice and career development. The working culture of young employees is different compared to previous generations. Being different, this cohort brings in the “job hop” phenomena into the workforce and the attitude has observed reduction in level of engagement towards organizations. Engaged employees are important in organizations to enable them to acquire more knowledge and become multi skilled human capital through indepth experience, with the assistance and support from mentor, coach and supervisor from the organizations. Scholars globally have been studied job satisfaction, job commitment, organizational citizenship behavior and the like among employees. However, there is still a dearth in studies to examine the relationship between employee engagement with organizational justice and organizational learning. This study examined the relationship between employee engagement with organizational justice and organizational learning, and the role of organizational image as mediator. The dependent variable was employee engagement, independent variables were organizational justice and organizational learning and organizational image was the mediating variable. For organizational justice, 3 dimensions were used in this study (1) distributive justice (2) procedural justice (3) interactional justice. Three dimensions were also used for organizational learning, (1) training (2) mentoring and (3) coaching. The underpinning theory used to support this study is the social exchange theory and socialization theory. The social exchange theory stated that organizations are forums for transactions where activities voluntarily exchange from individuals towards the organizations, while socialization theory stated that a protege who has a good relationship with his or her mentor tend t produce better work quality compare to protege who does not mentor. Results are in the form of positive outcome or otherwise and it depends on the perception of fairness felt by employees towards the organizations and good mentoring and training system that organization provide to employees. Sample used in this study are 413 young bankers from five commercial banks in Kuala Lumpur, Malaysia. Primary data were collected using survey questionnaire that was personally distributed to the participants at the participating banks. Data obtained were analyzed using SPSS. The type of study is a correlation study and the aim was to examine the variables that are associated with the problem instead of trying to establish the definitive cause and effect relationship. In examining the variables, a few types of analysis were conducted, (1) descriptive analysis (2) factor analysis (3) reliability test (4) response bias analysis (5) one-way ANOVA (6) correlation analysis and (7) multiple regression analysis. The results found indicated that employee engagement, the dependent variable, was conceptualized into two dimensions, i.e., engagement feelings and engagement loyalty. It also shows that (1) distributive justice, interactional justice, mentoring and training predict engagement feelings (2) only distributive justice predicts engagement loyalty; (3) organizational image partially mediates the relationship between distributive justice, interactional justice, mentoring and training with engagement feelings, and (3) organizational image partially mediates the relationship between distributive justice with engagement loyalty. The findings are useful in assisting Human Resource management team and Human Resource consulting firms in Malaysia to provide useful suggestions and recommendations in promoting the increase in level of engagement among young employees and ultimately contribute towards long term organizational success